An immune challenge reduces social grooming in vampire bats. (June 2018) - Stockmaier, Sebastian; Bolnick, Daniel I.; Page, Rachel A.; Carter, Gerald G.
Abstract : Social interactions affect the transmission of many pathogens, but infections often induce sickness behaviours that alter those interactions. Vampire bats are highly mobile and social, engaging in frequent allogrooming, which is likely to facilitate pathogen spread. Sickness behaviour is known to reduce social associations, but the effect on physical interactions between associated individuals, such as grooming, is less understood. Here, we tested the effects of induced sickness behaviour on allogrooming in vampire bats, while holding association between individuals in groups constant. To experimentally induce sickness behaviour, we used injections of lipopolysaccharide (LPS) and saline controls in 13 female common vampire bats, Desmodus rotundus, housed in stable groups of two to four adult bats. LPS injection induced an immune response that mimicked illness. Circulating leukocytes and neutrophil:lymphocyte ratios increased, while body mass and activity decreased. While LPS-injected bats did not receive less grooming from their group mates, they dramatically reduced the amount that they groomed their partners. This reduction in social interactions illustrates that sickness behaviour can potentially change transmission rates by altering directed behaviours, even under conditions of constant close proximity. The ability to manipulate social behaviours under controlled conditions should also prove useful for experiments attempting to test mechanisms underlying cooperation. Highlights: Sickness can affect animals' interactions and influence pathogen transmission. We examined captive female bats' responses to sickness using lipopolysaccharide. Sickened females groomed their cage mates far less. Sickness affected individuals' interactions even when proximity was controlled for. Induced sickness may allow testing of mechanisms underlying cooperation in animals.